2006
DOI: 10.1016/j.patcog.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Signatures versus histograms: Definitions, distances and algorithms

Abstract: Abstract. The aim of this paper is to present a new method to compare histograms. The main advantage is that there is an important time-complexity reduction respect the methods presented before. This reduction is statistically and analytically demonstrated in the paper. The distances between histograms that we present are defined on a structure called signature, which is a lossless representation of histograms. Moreover, the type of the elements of the sets that the histograms represent are ordinal, nominal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 22 publications
0
36
0
4
Order By: Relevance
“…Serratosa & Sanfeliu (2006) observed that most distance measures considers the overlap or intersection between two histograms as a function of the distance value, but they do not take accurately into account the similarity of the non-overlapping parts of the two histograms. The effects of these drawbacks are examined through the test case reported below.…”
Section: Histogram Matching Approach (Hma)mentioning
confidence: 99%
See 4 more Smart Citations
“…Serratosa & Sanfeliu (2006) observed that most distance measures considers the overlap or intersection between two histograms as a function of the distance value, but they do not take accurately into account the similarity of the non-overlapping parts of the two histograms. The effects of these drawbacks are examined through the test case reported below.…”
Section: Histogram Matching Approach (Hma)mentioning
confidence: 99%
“…It is an analysis of the frequency modification of each hydrologic variable from pre-to post-impact condition based on the Earth Mover's Distance (EMD) algorithm (Rubner et al, 1998(Rubner et al, , 2000 applied to "extended signatures" (Serratosa & Sanfeliu, 2006).…”
Section: Frequency Based Approach (Fba)mentioning
confidence: 99%
See 3 more Smart Citations